Implementation of Labor Law in the Era of Industrial Revolution 4.0 - Challenges and Solutions - Bachrul Amiq; Wahyu Prawesthi; Noenik Soekorini; Hartoyo Hartoyo; Sri Astutik (PT. Banjarese Pacific Indonesia, 2024)
The Industrial Revolution 4.0 has drastically transformed global industries, introducing advanced technologies such as automation, artificial intelligence, and digitalization into the workplace. This rapid technological shift has presented significant challenges for labor laws, which are often designed for traditional work environments. This study explores the implementation of labor law in the context of the Industrial Revolution 4.0, analyzing the challenges faced by both employers and employees in adapting to these new technological advancements. Using a qualitative methodology, this research employs a juridical review of existing labor laws, supported by an in-depth case study examining how these laws are applied in technology-driven industries. The findings indicate that labor laws often lag behind the technological advances, leading to gaps in legal protections for workers and ambiguities in employer obligations. The case study highlights specific instances where current labor regulations fail to address issues related to remote work, job displacement due to automation, and workers' rights in the gig economy. Solutions are proposed to modernize labor laws, ensuring they are adaptable to future technological developments while safeguarding workers' rights. The study concludes that there is an urgent need for legal reforms to balance innovation with fair labor practices in the era of Industry 4.0.